Somalia Economic Update, June 2020 : Impact of COVID-19 - Policies to Manage the Crisis and Strengthen Economic Recovery - World Bank (World Bank, Washington, DC, 2020)
Before the COVID-19 (Coronavirus) pandemic, Somalia’s economy was on an upward trajectory, recovering from the 2016/17 drought. The economy grew at an estimated rate of 2.9 percent in 2019, on par with population growth, and was projected to grow at 3.2 percent in 2020. The COVID-19 pandemic has interrupted Somalia’s economic recovery. The crisis will have a large negative impact on real GDP growth in 2020, affecting the economy through a combination of supply and demand shocks. As a result of shutdowns, global supply chains have disrupted imports of consumption and capital goods from Somalia’s trading partners (mainly China, the United Arab Emirates, India, Turkey, and Oman); cancellations of the 2020 Hajj and export bans by Saudi Arabia have tamped down demand for exports (mostly live animals); and the global recession and travel restrictions/flight suspensions are limiting remittance flows into Somalia. The economy, which is driven mainly by the private sector, is exposed to increased business vulnerabilities, interruption of supply chains, decreased capital and venture inflows, diminished access to financing, and shortages of basic raw materials. The pandemic is projected to push the economy into contraction, increase fiscal pressures, and deepen poverty in 2020. The economy is projected to contract by 2.5 percent in 2020. A slowdown in economic activities, declining remittances, falling exports, and the government-mandated closures of airports and businesses to contain the spread of the virus are reducing household income. Household consumption will fall sharply and rapidly with supply disruptions. Panic buying led to an uptick in prices in an economy that depends on imports even for food products at the start of the pandemic, but this has eased.